Spindle Cell Lipoma: A Case Report And Review Of Literature - Chandrashekar, P; Jose, M; Dadhich, M; Chatra, L; Holla, V (Kathmandu University Medical Journal, 2013)
Oral spindle cell lipoma is a rare lesion and until now only 26 cases have been reported in English literature. In this article we report a case of oral spindle cell lipoma presented to our institution in July 2011, as an asymptomatic solitary growth of the buccal mucosa in a 58 year old male patient. On histopathological examination the lesion exhibited an admixture of adipocytes and spindle cells with collagen fibres and numerous mast cells. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 92-95 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7353